Digital literacy in a post Coronavirus era: a management perspective for small businesses in Africa - Arachie Augustine Ebuka; Hope Ngozi Nzewi; Emejulu Gerald; Kekeocha Mary Ezinne (Annals of Management and Organization Research)
Purpose: This study examined how small businesses in Africa can use technology to grow and sustain their businesses in a post-Covid-19 world. The paper looked at various digital skills needed by these businesses to navigate and profit from the digital space's massive opportunities. It also ascertained the challenges facing them from keying into the digital ecosystem. The place of technology in the fight against Covid-19 was also highlighted. Research methodology: This study is a qualitative review study. Results: The study concluded that possessing some form of digital skills by business owners and employees could be the difference between a competing and a non-competing organization. Limitations: The work did not use methodology as it is a qualitative review study that limited the study's generalizability. Contribution: This work represents a current work in digital technology and how it relates to pandemic situations and economic challenges, especially in Africa. Keywords: Digital, Technology, Covid-19, Small businesses, Management, Skills